2007
DOI: 10.1016/j.jri.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of p38 MAP kinase in lipopolysaccharide-induced production of pro- and anti-inflammatory cytokines and prostaglandin E2 in human choriodecidua

Abstract: Chorioamnionitis is implicated in the pathogenesis of preterm delivery. However, the detailed mechanisms by which infection induces preterm labor are not well understood. This study has assessed the involvement of mitogen-activated protein (MAP) kinases in lipopolysaccharide (LPS)-induced pro- and anti-inflammatory cytokine and prostaglandin (PG) production in human choriodecidua. Samples of choriodecidua were collected before the onset of labor from women undergoing elective cesarean sections at term for bree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
34
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 19 publications
7
34
0
Order By: Relevance
“…It is not surprising then to see that SB202190 was able to suppress secretion of these inflammatory cytokines and mediators. Shoji et al previously reported involvement of the MAPK pathway in the production of proinflammatory cytokines in the choriodecidua (55)(56)(57). What was unexpected was that BAY 11-7082, an NF-κB inhibitor, did not have a significant effect on the secretion of these cytokines in results, together with our cell viability assays, served as the basis for using 10 mM as the highest concentration in the in vitro experiments here.…”
Section: Dma Inhibits the Transcriptional Activity Of Nf-κb But Not Asupporting
confidence: 54%
“…It is not surprising then to see that SB202190 was able to suppress secretion of these inflammatory cytokines and mediators. Shoji et al previously reported involvement of the MAPK pathway in the production of proinflammatory cytokines in the choriodecidua (55)(56)(57). What was unexpected was that BAY 11-7082, an NF-κB inhibitor, did not have a significant effect on the secretion of these cytokines in results, together with our cell viability assays, served as the basis for using 10 mM as the highest concentration in the in vitro experiments here.…”
Section: Dma Inhibits the Transcriptional Activity Of Nf-κb But Not Asupporting
confidence: 54%
“…Its similar potency to TPCA-1 in the ovine explant model would argue against the latter hypothesis. To date, no studies have characterised the expression and activity patterns of MAPKs during inflammation in human gestational membranes, although MAPKs are known to respond to infectious stimuli and regulate the production of pro-inflammatory cytokines (Underwood et al 2000, Barone et al 2001, Ward et al 2001, Ju et al 2002, Shoji et al 2007. Regardless, our results highlighted SB239063 as a potentially effective anti-inflammatory agent useful for preventing inflammation-driven PTB.…”
Section: Discussionmentioning
confidence: 66%
“…In fact, PKA can phosphorylate diverse transcription factors leading to the synthesis of mRNAs for several target genes, including COX-2 [31]. The FSH signaling pathway can also diverge, at the level of PKA to activate other downstream targets such as the extracellular-regulated kinases and p38 MAPK (mitogen-activated protein kinases) in the MAPK signaling pathways [32,33], as has been observed in human chorion-decidua [34] and myometrial smooth muscle cells [35]. However, the existence of several alternative pathways through which FSH could stimulate the expression of COX-2 does not explain its failure to increase the concentration of PGE 2 in the culture media.…”
Section: Discussionmentioning
confidence: 93%